Sincronización del sistema de tracción del proceso de recubrimiento con polietileno de los coils que conforman los catéteres para la empresa Boston Scientific Costa Rica - Monge-Jiménez, Luis Eduardo (Instituto Tecnológico de Costa Rica, 2012)
The company Boston Scientific Costa Rica is engaged in the manufacturing of medical products at the areas of urology, cardiology and endoscopy. One is the biopsy catheter, consisting of a handle, a coil and forceps. The coil is a tubular shape and flexible spiral, made of stainless steel and coated with a layer of polyethylene. Currently, the process of coating the coils with polyethylene is done automatically, in an extrusion line which has three drive shafts that carry the coils through the process phases. However, there are problems of quality because the coating is not remain homogeneous, presenting a thickness less than the acceptable or even exposed areas of the coil’s stainless steel. This forces to discard several batches of the product, generating economic losses to the company, It was determinate that the problem is due the lack of coordination between the principal drive shaft, the extruder machine worm and the other two drive shafts. Thus, it is required to design and implement an automatic control system for the drive shafts speed; using the variable frequency drives (VFD) that handles those shafts, the programmable logic controller (PLC) which governs the entire extrusion line and feeding back the worm’s shaft state through the Profibus communication network. Finally the achieved improvement in the coating process must be analyzed, which is related with an increase in the probability to obtain a product that meets the company’s quality standards.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: Control de calidad; Materiales; Acero inoxidable; Polietileno; Controles programables; Redes de comunicación; Profibus DP